Analysis of the Relationship between Maternal Parenting, Father's Role, and the Incidence of Stunting on the Development of Children Aged 24-59 Months in Palembang City - Nadia Sara Anggraini; Amrina Rosyada (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
The golden period is very important to optimize the various potentials of children's intelligence so that children can be in the appropriate growth and development as a determinant of their quality of life. The golden period is the most important period of growth and development in a child's life that occurs in the first 5 years of life. This study aims to analyze the relationship between maternal parenting, father's role, and the incidence of stunting on the development of children aged 24-59 months in Palembang City. This study used a cross-sectional design with a sample of families who had children under five years of age 24-59 months which is located at the research site. The location of this research was carried out in Sukarami District, Ilir Barat 1 District, Kemuning District and Alang-alang Lebar District of Palembang City. The research began on June 16 and ended on July 10, 2023. This research uses a quantitative approach The results showed that there was a significant. relationship between maternal parenting and child development aged 24-59 months (p-value = 0.000) PR: 2.543, there was a significant relationship between father's role and child development aged 24-59 months (p-value = 0.005) PR: 1.773 and there was no significant relationship between the incidence of stunting and child development aged 24-59 months (p-value = 0.262). The conclusion of this study shows that there is a relationship between maternal parenting and a father's role on the development of children aged 24-59 months in Palembang City, and there is no relationship between the incidence of stunting and the development of children aged 24-59 months in Palembang City. The researcher suggested that Parents should actively work together to monitor their children's development and that health workers should create a public health program by involving the father's contribution in parenting.Keywords : Child development, Father's role, Maternal parenting, Stunting